The Role of Information Technology in Improving the Quality of Social Studies Learning in Elementary Education - Ester, Kartini; Kertih, I Wayan; Lasmawan, I Wayan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to explore the effect of technology utilization on increasing fourth-grade students' interest and motivation in learning social studies. The research method used was qualitative with a phenomenological approach, involving 22 students at elementary school 2 Tomohon. Data was collected through semi-structured interviews, classroom observations, and group discussions. The results showed that the use of technology, such as tablet devices and interactive educational applications, significantly increased students' interest and motivation. As many as 85% of students stated that technology made learning more interesting, while 78% felt more motivated to learn. In addition, student participation in discussions also increased, and they developed useful digital skills. However, challenges such as limited access and unstable internet connections need to be addressed. These findings suggest that integrating technology in social studies learning can create a more interactive and effective learning environment and provide recommendations for the development of better educational practices. Based on the results of the research conducted, it can be concluded that the use of technology in social studies learning makes a significant contribution to increasing students' interest and motivation to learn, where 85% of students stated that the use of technology makes social studies lessons more interesting, while 78% of students feel more motivated to learn when technology is used in learning activities.